2013
DOI: 10.1002/hep.26684
|View full text |Cite
|
Sign up to set email alerts
|

Pre-transjugular intrahepatic portosystemic shunts (TIPS) prediction of post-TIPS overt hepatic encephalopathy: The Critical Flicker Frequency is more accurate than psychometric tests

Abstract: Transjugular intrahepatic portosystemic shunts (TIPS) is a second-line treatment because of an increased incidence of overt hepatic encephalopathy (OHE). A better selection of patients to decrease this risk is needed and one promising approach could be the detection of minimal hepatic encephalopathy (MHE). The aim of the present prospective study was to determine whether pre-TIPS minimal hepatic encephalopathy was predictive of post-TIPS OHE and to compare Psychometric Hepatic Encephalopathy Sum Score (PHES) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 35 publications
1
53
1
Order By: Relevance
“…In a later study, by another group, a CFF cut-off of 38 Hz identified patients with minimal hepatic encephalopathy, diagnosed using the PHES test, with a sensitivity of 72.4 % and a specificity of 77.2 % and an observed agreement of 75 % (Romero-Gómez et al 2007). Low CFF readings predict the development of overt hepatic encephalopathy during follow-up (Romero-Gómez et al 2007); predict the development of overt hepatic encephalopathy following TIPS insertion more accurately than the PHES test (Berlioux et al 2014); and predict poor post-TIPS outcomes (Kircheis et al 2009). Variables such as gender, level of education and time of day do not appear to significantly affect CFF results (Kircheis et al 2002), although there is some evidence of differential effects in relation to age (Dhiman et al 2010;Goldbecker et al 2013) and the aetiology of the underlying liver disease (Kircheis et al 2002).…”
Section: Other Assessment Techniquesmentioning
confidence: 99%
“…In a later study, by another group, a CFF cut-off of 38 Hz identified patients with minimal hepatic encephalopathy, diagnosed using the PHES test, with a sensitivity of 72.4 % and a specificity of 77.2 % and an observed agreement of 75 % (Romero-Gómez et al 2007). Low CFF readings predict the development of overt hepatic encephalopathy during follow-up (Romero-Gómez et al 2007); predict the development of overt hepatic encephalopathy following TIPS insertion more accurately than the PHES test (Berlioux et al 2014); and predict poor post-TIPS outcomes (Kircheis et al 2009). Variables such as gender, level of education and time of day do not appear to significantly affect CFF results (Kircheis et al 2002), although there is some evidence of differential effects in relation to age (Dhiman et al 2010;Goldbecker et al 2013) and the aetiology of the underlying liver disease (Kircheis et al 2002).…”
Section: Other Assessment Techniquesmentioning
confidence: 99%
“…Bearing in mind these limitations, the incidence of overt episodic or recurrent HE post-TIPS varies between 15 and 67% in a 2-year follow-up. The incidence of persistent overt HE is around 8% [80] and that of de-novo, covert HE around 35% [14,26,[81][82][83][84][85][86][87][88]. [31,81,82,84] • Baseline arterial hypotension (1a) [4,83] • High serum creatinine and hyponatriemia (Na < 130) (1a) [4, 80,82] • Low serum albumin levels (1b) [80] • Bare vs. covered stent (2b) [85] • Very low porto-systemic pressure gradient after TIPS (<5 mmHg) (1a) [25,[78][79][80][81][82][83]87] a Child A risk of HE close to 0, in Child B up to 33%, in Child C up to 89%.…”
Section: Is There a Risk For Hepatic Encephalopathy After Tips?mentioning
confidence: 99%
“…The second major complication is recurrent portal hypertension secondary to development of in-stent stenosis, despite improved patency with the advent of covered stents (7,8). Therefore, comprehensive and longitudinal hemodynamic monitoring of the portal system and the TIPS is needed to monitor stent patency and the fraction of blood flow that is diverted from the liver (9,10). …”
mentioning
confidence: 99%